1984
DOI: 10.1017/s0022172400064822
|View full text |Cite
|
Sign up to set email alerts
|

An outbreak of calicivirus associated gastroenteritis in an elderly persons home. A possible zoonosis?

Abstract: An outbreak of gastroenteritis caused by calicivirus began amongst residents and staff of an old persons home 24 hours after the proprietor's dog had been sick. Serological evidence suggests that the calicivirus isolated from one of the cases may be capable of infecting dogs as well as man. The virus strain responsible for this outbreak differs antigenically from those associated with two other outbreaks in the U.K. and one in Japan. The characteristic morphology of calicivirus is lost if stool is stored at -7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
1

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 9 publications
0
23
1
Order By: Relevance
“…1) (1). Sapovirus particles were first detected in human diarrheic stool samples in 1976 in the United Kingdom using electron microscopy (EM) (2), and the virus was soon recognized as a new gastroenteritis pathogen (3)(4)(5)(6)(7)(8)(9)(10)(11). However, the prototype strain of the Sapovirus genus was from another outbreak in Sapporo, Japan, in 1982 (strain Hu/SaV/Sapporo/1982/JPN), because it has been studied extensively for sapovirus virological and genetic characteristics (10,(12)(13)(14).…”
Section: Historymentioning
confidence: 99%
See 1 more Smart Citation
“…1) (1). Sapovirus particles were first detected in human diarrheic stool samples in 1976 in the United Kingdom using electron microscopy (EM) (2), and the virus was soon recognized as a new gastroenteritis pathogen (3)(4)(5)(6)(7)(8)(9)(10)(11). However, the prototype strain of the Sapovirus genus was from another outbreak in Sapporo, Japan, in 1982 (strain Hu/SaV/Sapporo/1982/JPN), because it has been studied extensively for sapovirus virological and genetic characteristics (10,(12)(13)(14).…”
Section: Historymentioning
confidence: 99%
“…Based on the epidemiological data from patients with sapovirus gastroenteritis, the incubation period ranges from less than 1 day to 4 days (5,8,44,130,135,178,183,184). Major clinical symptoms include diarrhea and vomiting; however, additional constitutional symptoms (i.e., nausea, stomach/abdominal cramps, chills, headache, myalgia, or malaise) are also frequently reported.…”
Section: Symptoms and Severity Of Diseasementioning
confidence: 99%
“…12 Thus far, to our knowledge, no HuNoVs have been detected in pets, although several years ago a report suggested that a sick dog caused an NoV outbreak in a retirement home in the UK. 13 …”
Section: Introductionmentioning
confidence: 99%
“…Occasionally SaV outbreaks occur in the elderly in nursing homes Humphrey et al, 1984;Gray et al, 1987;Simor et al, 1990], but rarely in adults under 65 years of age, although an outbreak involving teachers in a school in the USA [Noel et al, 1997] and a nosocomial outbreak affecting adult patients and medical staff [Johansson et al, 2005] have been reported. Sporadic cases of SaV gastroenteritis in adults occur occasionally and have been reported in Japan [Okada et al, 2002] and the UK (this study).…”
Section: Introductionmentioning
confidence: 99%